(untitled) (Journal of Academic Research, 2017)
Health care–associated infections persist as a major problem in most neonatal intensive care units (NICU). Hand hygiene has been sing out as the most important measure in preventing hospital-acquired infection. However, hand hygiene compliance among health care workers (HCWs) remains low. At this study fifteen clinical isolates were pecked from hands of nine staff nurses at the NICU of Misurata central hospital. They were identified by using API 20E system as following: Staphylococcus aureus, 8; Enterobacter cloacae, 2; Enterobacter sakazakii, 2; Enterobacter amnigenus, 2; Acinetobacter bummanii, 1. Staphylococcus aureus was the most predominant bacteria carried by nurse’s hands (53.34). Tetracycline was found the most effective antibiotic for these isolates except Enterobacter cloacae which was sensitive to gentamycin in this study